ANALISIS KINERJA KEUANGAN DITINJAU DARI ASPEK RISIKO LIKUIDITAS, RASIO RENTABILITAS, DAN RASIO PERMODALAN PADA PT BANK DANAMON INDONESIA Tbk. PERIODE TAHUN 2014-2018 - Anis Rahma Ayuningtyas; Prihatiningsih Prihatiningsih; Nina Woelan Soebroto (FInance and Banking Program, Accounting Department, Politeknik Negeri Semarang, 2020)
This study aims to describe the results of the ranking and calculation of bank financial performance based on Liquidity Risk, Profitability Ratio and Capital Ratio at PT Bank Danamon Indonesia Tbk. period of 2014 - 2018. This Final Project uses descriptive writting method with a qualitative and quantitative approach and in collecting data using the published documentation method. This study uses secondary data obtained from PT Bank Danamon Indonesia Tbk. in the form of financial statements. Variables in this study are on liquidity risk using a Loan to Deposit Ratio (LDR), profitability ratio using Return On Assets (ROA) and Net Interest Margin (NIM). ), while the capital ratio uses the Capital Adequacy Ratio (CAR). The results of the study show that financial performance at PT Bank Danamon Indoneisa Tbk. period of 2014 - 2018 viewed from liquidity risk (LDR) is ranked 3 (three) or Moderate. ROA is ranked 1 (one) or very adequate in 2014, in 2015 was ranked 2 (two) or adequate, and in 2016-2018 was ranked 1 (one) or very adequate. NIMs in 2014-2018 were ranked 1 (one) or very adequate even though they experienced an increase and decrease in the value of the ratio and CAR in 2014-2018 was ranked 1 (one) or very adequate. The results of this study are expected to provide an overview to the bank stakeholders regarding the soundness of the bank.